LOGISTICS AND EFFICIENCY OF HEAVY TRAFFIC - Oksana D. Pokrovskaya; Oleg V. Shugaev (International Journal of Advanced Studies)
Background. The article is devoted to the study of the organization of the heavyweight movement. The relevance of the topic is related to the steady increase in the average weight of freight trains operating on heavily loaded routes of Russian railways and the corresponding need for a comprehensive assessment of the potential of heavy traffic.